Pengaruh Penerapan E-filing terhadap Kepatuhan Pelaporan Wajib Pajak dengan Media Sosial sebagai Variabel Moderasi - Celintara Anindya Ayu Wardhani; Sarah Kristina; Priyo Hari Adi (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2020)
This study aims to analyze the effect of applying e-filing to taxpayer reporting compliance with the use of social media as a moderating variable. The data used are primary data in the form of questionnaires taken directly through filling out questionnaires distributed via online media using Google Form. The sampling method in this study uses a purposive sampling method with taxpayer criteria using social media. The results showed that the application of e-filing had a significant positive effect on compliance with taxpayer reporting while the use of social media was not able to moderate the effect of e-filing on taxpayer reporting compliance.